Enhancing Customer Relationship Management in MSMEs: The Impact of Social Media Marketing on Performance Marketing - Huda, Farah Azzahra; Praswati, Aflit Nuryulia (Proceeding ISETH (International Summit on Science, Technology, and Humanity), 2023)
Objective: MSMEs play an important role in economic development in Indonesia. There are several things that MSMEs in Indonesia have not developed, one of which is weak human resources and limited capabilities in terms of marketing. Therefore, social media is needed to overcome this problem. The aim of this research is that with social media marketing, MSME business actors in Indonesia can develop in terms of marketing performance which is useful for involving MSME business actors with a wider range of customers and establishing relationships with customers so that customers are better looked after. loyal to MSME products through customer relationship management. Methodology: This research uses a quantitative research approach and collects primary data using online questionnaires via Google form and offline, namely directly to outlets, then collecting a sample of 100 MSME business actors in the fashion industry, culinary and craft industries, then processing the data using the SEM PLS application. Results: This study states that social media marketing has a positive impact on marketing performance and social media marketing has a positive impact on customer relationship management. Therefore, customer relationship management has a positive impact on marketing performance. MSME businessmen feel supported by social media marketing. Social media allows MSME businessmen to increase sales, compete with competitors, and increase customer loyalty to their products. Application/Authenticity/Value: The data that has been processed in this research is different from previous research, namely that 100 respondents can represent the results of social media marketing users among MSME business actors. Apart from that, this research uses different variables from the previous one by combining the influence of social media marketing for marketing performance on customer relationship management in MSMEs.